Synthesis, characterization, conformational study and antibacterial activity of N-acylhydrazones - Khong, Pek Yao (2023)
Researchers have put so much effort in N-acylhydrazones recently due to their biological activities such as antibacterial, antitumor, anticancer, antioxidant and anti-inflammatory. A series of new N-acylhydrazone derivatives SB 1- SB 10 were synthesized in yields ranging from 52 to 78% through the reactions of carboxylic acid hydrazide with a variety of substituted benzaldehydes. The structures of the synthesized compounds were confirmed by IR, 1H- and 13C NMR, DEPT, NOE, HMQC and HMBC spectral data. From the relative configuration of imine double bond and the conformation of CONH bond of synthesized compounds, the C=N double bonds of N-acylhydrazones showed (E)-configuration, while the NMR data of all synthesized N-acylhydrazones indicated the existence of cis-/trans- conformers for each compound in DMSO-d6. In N-acylhydrazones SB 1 – SB 5, the signals of the cis- and trans amide conformers coalesced as the temperature increased between 298 and 373 K. The synthesized compounds were evaluated for their antibacterial activities against three microbial strains which were two Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) and one Gram-negative ii bacteria (Pseudomonas aeruginosa). The result suggested that SB 1 - SB 9 exhibited poor antibacterial activities against all tested bacteria strain. Particularly, compound SB 10 (2- OH, 4NEt2) showed moderate antibacterial activity against Gram-negative bacteria Pseudomonas aeruginosa at MIC value of 62.5 µg/mL